Avaliação da participação do hipocampo dorsal na plasticidade sináptica associada à expressão de pCREB nos núcleos da amígdala após a tarefa de esquiva inibitória - Favaro, Vanessa Manchin [UNIFESP] (2019)
The Inhibitory Avoidance (IA) - step-through and contextual fear conditioning (CFC) tasks are based on different types of associative learning, in which memories related to aversive events can be studied. The both tasks involve the association between stimuli, the conditioned stimulus, which can be the context where the animal is placed, and the unconditioned, as a foot shock, related to the fear conditioning. In particular, only the task of IA also involves the association between a behavior and a stimulus, this type of learning is relative to the instrumental conditioning. It is known that both tasks depend on the involvement of the amygdala, while the involvement of the hippocampus depends on the salience of contextual and spatial components present in these tasks. An earlier study from our laboratory showed that temporary dorsal hippocampal blockade not only decreased the animals' defensive behaviors in CFC but also decreased the expression of the phosphorylated cAMP response element binding protein (pCREB), a related transcription factor to synaptic plasticity and memory, in the amygdala nuclei. In this sense, the present study investigated the participation of the dorsal hippocampus in the synaptic plasticity associated with pCREB expression in the amygdala nuclei after the IA task. In Phase 1, significant differences were observed in the defensive behaviors, particularly in latency, freezing time in the white compartment and in the time in activity in animals submitted to immediate shock and the condition of habituation in the IA task. In addition, an increase in pCREB expression was observed in the lateral, basolateral and central nuclei of the amygdala after the EI-step-through task. In Phase 2, the results of the pharmacological experiments showed that the manipulation of different classes of hippocampal receptors did not affect the performance of the animals in the step-through IA task. In agreement with the pharmacological results, data obtained with the immunohistochemical technique showed that the expression of pCREB in the lateral, basolateral and central nuclei of the amygdala is independent of the participation of the hippocampus. Taken together, our results suggest that the interaction between hippocampus and amygdala in the step-through IA task is different when compared to CFC, possibly due to the instrumental component of learning.